2001
DOI: 10.1542/peds.108.2.e34
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and Childhood Behavior at Age 6 to 7 Years: I. Dose-Response Effect

Abstract: ABSTRACT.Objective. Moderate to heavy levels of prenatal alcohol exposure have been associated with alterations in child behavior, but limited data are available on adverse effects after low levels of exposure. The objective of this study was to evaluate the dose-response effect of prenatal alcohol exposure for adverse child behavior outcomes at 6 to 7 years of age.Methods. Beginning in 1986, women attending the urban university-based maternity clinic were routinely screened at their first prenatal visit for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
288
2
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 414 publications
(316 citation statements)
references
References 25 publications
15
288
2
11
Order By: Relevance
“…Importantly, however, well over half (63%) of the women who continued to drink alcohol fell into the lightest level of drinking (<1 day/week) and another 27% were drinking 1 to 2 days per week. These are levels at which recent studies indicate substantial risk for the child, 8 but these are women who most often are missed in routine prenatal care and through other forms of screening. The rate of admitted marijuana use only in the month prior to knowledge of pregnancy among the population of 4865 women in the four clinics was 7%, and 3% of the total population continued to use marijuana after knowledge of pregnancy (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, however, well over half (63%) of the women who continued to drink alcohol fell into the lightest level of drinking (<1 day/week) and another 27% were drinking 1 to 2 days per week. These are levels at which recent studies indicate substantial risk for the child, 8 but these are women who most often are missed in routine prenatal care and through other forms of screening. The rate of admitted marijuana use only in the month prior to knowledge of pregnancy among the population of 4865 women in the four clinics was 7%, and 3% of the total population continued to use marijuana after knowledge of pregnancy (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have found poor pregnancy and neonatal outcomes among women who used alcohol or illegal drugs during pregnancy, [1][2][3][4] and the long-term impact of prenatal alcohol or illicit drug exposure on the development and behavior of the exposed child [5][6][7][8] is now being documented. However, despite the concern over the consequences of prenatal exposure to alcohol and other drugs, substance use by the pregnant woman remains a frequently missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The approach is also consistent with prior studies of the association of child behavior problems with SES, 27 maternal smoking, 28 depressive symptoms, 29 and alcohol use. 30 The BPI externalizing subscale has good internal validity (Cronbach's alpha 0.85) and correlates well with the CBCL equivalent. 31 Scores are standardized to a mean (standard deviation [SD]) of 100 (Ϯ15).…”
Section: Study Variablesmentioning
confidence: 94%
“…Alcohol consumption during pregnancy has been associated with many harmful effects in the developing fetus. Most studies have focused on neurodevelopmental (Riley and McGee, 2005;West and Blake, 2005) and behavioral anomalies (Mattson et al, 2001;Sood et al, 2001) in infants born from mothers who drank during pregnancy. Recently it has been suggested that in addition to neurodevelopmental effects, ethanol may play a significant role in immunomodulation and consequential increase in susceptibility to various infectious in newborn infants (Gauthier et al, 2005a;Gauthier et al, 2004;Gauthier et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%